The role of SCUBE1 in the development of late stent thrombosis presenting with ST-elevation myocardial infarction - Hasan Ata Bolayır (Revista Portuguesa de Cardiologia, 2018)
Introduction and Aim: There is an important link between platelets and inflammation, thrombosis, and vascular and tissue repair mechanisms. SCUBE1 (signal peptide-CUB-EGF domain-containing protein 1) may function as a novel platelet-endothelial adhesion molecule and play pathological roles in cardiovascular biology. Stent thrombosis (ST) following percutaneous coronary intervention is an uncommon and potentially catastrophic event that can manifest as myocardial infarction and sudden death. High platelet reactivity is a risk factor for thrombotic events, including late ST. For this reason, in the current study, we researched the role of SCUBE1 in the development of late coronary ST. Methods: We included 40 patients admitted to our hospital with a diagnosis of ST-elevation myocardial infarction (STEMI) and signs of late ST on a coronary angiogram. For the control group, we recruited 50 healthy gender- and age-matched individuals who were seen for health check-ups. We also randomly included 100 patients with a diagnosis of STEMI without ST. Results: There were no significant differences between the groups in terms of baseline and demographic characteristics. The mean SCUBE1 level in patients with STEMI with late ST at admission and the STEMI without ST group was significantly higher than in the control group (p<0.01). The mean SCUBE1 level in the STEMI with late ST group was significantly higher than in the STEMI without ST group (p=0.03). In multivariate regression analysis, serum SCUBE1 (odds ratio [OR]: 1.022; 95% confidence interval [CI]: 1.011-1.033, p<0.001) remained an independent predictor for the presence of late ST. In addition, receiver operating characteristic curve analysis was used to determine the optimal SCUBE1 cut-off value for predicting late ST. The area under the curve was 0.972 (95% CI 0.95-0.98). The SCUBE1 cut-off value was 59.2 ng/ml, with a sensitivity of 95.4% and specificity of 82.9%. Conclusion: The present work is the first clinical study to demonstrate that serum SCUBE1 levels are significantly higher in patients with late ST and serum SCUBE1 was an independent predictor for the presence of late ST in our study population. Resumo: Introdução e objetivos: Existe uma ligação importante entre plaquetas e inflamação, trombose e mecanismos de reparação tecidular e vascular. O biomarcador SCUBE1 [signal peptide-CUB (complement C1r/C1 s)-EGF (epidermal growth factor like domain-containing protein 1)] pode funcionar como uma nova molécula de adesão plaqueta-endotélio e pode ter papéis patológicos na biologia cardiovascular. A trombose de stent (TS) no seguimento de uma intervenção coronária percutânea é um evento incomum e potencialmente catastrófico que se pode manifestar como enfarte do miocárdio e morte súbita. A reatividade plaquetária elevada é um fator de risco para eventos trombóticos, inclusive a TS tardia. Por esse motivo, no presente estudo, investigámos o papel do biomarcador SCUBE1 no desenvolvimento da TS tardia nas coronárias. Métodos: Incluímos 40 doentes, admitidos no nosso hospital, com diagnóstico de enfarte do miocárdio com elevação do segmento ST (STEMI) e sinais de TS tardia na angiografia coronária. Para o grupo de controlo, reunimos 50 indivíduos saudáveis controlados para género e idade que foram submetidos a exames de rotina. Aleatoriamente incluímos também 100 doentes com diagnóstico de STEMI sem elevação do segmento ST. Resultados: Não houve diferenças significativas entre os grupos no que se refere aos valores basais e às características demográficas. O nível médio do biomarcador SCUBE1 no grupo com STEMI e com elevação tardia de TS no momento do internamento e do grupo com STEMI sem elevação do segmento ST foi significativamente superior ao do grupo controlo (p < 0,01). O nível médio do biomarcador SCUBE1 no grupo de STEMI com TS tardia foi significativamente superior ao do grupo de STEMI sem elevação de ST (p = 0,03). Na análise de regressão multivariável, o nível sérico do biomarcador SCUBE1 [odds ratio (OR): 1,022; intervalo de confiança (IC) 95%: 1,011-1,033, p < 0,001] permaneceu como um fator preditor independente na presença de TS tardia. Além disso, a análise da curva ROC foi usada para determinar o valor cut-off do biomarcador SCUBE1 aprimorado para diagnóstico de TS tardia. O valor da área sob a curva (ASC) foi 0,972 (intervalo de confiança (IC) 95%: 0,95-0,98). O valor cut-off do biomarcador SCUBE1 foi 59,2 ng/ml com uma sensibilidade de 95,4% e uma especificidade de 82,9%. Conclusões: O presente estudo é o primeiro estudo clínico que demonstra que os níveis séricos do biomarcador SCUBE1 são significativamente superiores nos doentes com TS tardia e que o nível sérico do biomarcador SCUBE1 é um fator preditor independente para a presença de TS tardia na população do estudo. Keywords: SCUBE1, Platelet activation, Stent thrombosis, Palavras-chave: SCUBE1, Ativação plaquetária, Trombose de stent